Faktor-Faktor yang Berhubungan Dengan Perilaku Pencegahan Diare di Kecamatan Kemayoran, Jakarta Pusat, Tahun 2025 dan Tinjauannya Menurut Pandangan Islam - Utami, Miranda Laras; Ernawati, Kholis; Wulansari, Rifda; Anshar, M. Fazlurrahman (Jurnal Impresi Indonesia, 2025)
Diarrhea remains a significant health problem in Indonesia, with a high prevalence in densely populated areas. In 2018, Jakarta was recorded as the region with the highest number of cases. Diarrhea prevention is strongly influenced by predisposing, enabling, and reinforcing factors. This study used an observational analytical design with a cross-sectional approach, involving 106 respondents. Results showed that the majority of respondents were aged 18–25 years (37.7%), female (66%), and worked in the informal sector (64.2%). Most had good knowledge (68.9%), a positive attitude (64.2%), good sanitation (52.8%), and family support (52.8%). Diarrhea prevention behavior was predominantly in the good category (54.7%). Bivariate analysis showed a significant relationship between all these factors and prevention behavior. Knowledge, attitude, home sanitation, and family support showed a strong correlation. The conclusion of this study is that predisposing, enabling, and reinforcing factors play an important role in diarrhea prevention behavior, with knowledge, attitude, sanitation, and family support being the strongest factors. These findings emphasize the importance of strengthening family-based PHBS education that aligns with Islamic values ??of purity and cleanliness, as well as the need for cross-sector interventions to improve sanitation and preventative behavior in the community.